Change in Systolic Blood Pressure During Stroke, Functional Status, and Long-Term Mortality in an Elderly Population - Weiss, Avraham (Am J Hypertens, 2016)
BACKGROUND: Elevated systolic blood pressure (SBP) recorded by 24-hour blood pressure monitoring (24H BPM) on the first day of acute stroke is associated in elderly patients, with an unfavorable outcome. Herein, we assessed, by 24H BPM, the impact of the change in SBP levels during the first week of stroke on short-term functional status and long-term mortality in elderly patients. METHODS: One hundred and fifty acute stroke patients (69 males), mean age at admission 83.6±5.5 years, 82% with ischemic stroke, were investigated. 24H BPM was recorded within 24 hours of admission and 1 week later. After 7 days, patients were assessed for functional status according to the modified Rankin scale (mRS) and were subsequently followed for mortality up to 7.5 years (mean 3.16±2.29). RESULTS: After 7 days, SBP decreased from 147±21 to 140±20mm Hg (P < 0.001). Functional status improved and mRS decreased from 4.2 to 3.7. During follow-up, 58 patients (17 males and 41 females) had died. Mortality rate was higher in females (69% vs. 45%; P < 0.01) and in patients with a history of congestive heart failure. The average admission SBP predicted short-term functional status and long-term mortality. However, the change in SBP corrected for admission levels, gender, age and other variables was not associated with short-term functional status and long-term mortality. CONCLUSION: There is no evidence of association between change in SBP during the first week of stroke and short-term functional status and long-term mortality in this group of stroke patients.